The Role of Stickers in Workplace Apologies: A Study of Perceived Justice and Relationship Repair - Cheng, Fei-Fei; Wu, Yu-Chen; Yang, Fu-Chu; Wu, Chin-Shan (International journal of human-computer interaction, 2025)
This study examines whether using stickers in workplace apologies effectively conveys the sender's attitude and influences the receiver's perception of justice, post-apology satisfaction, and trust. Adopting the receiver's perspective, it investigates how different sticker types used across workplace communication directions (horizontal, downward, upward) affect fairness perceptions and the moderating role of the receiver's gender. A 3 × 4 within-subjects design was employed (communication direction × sticker type: cute, ugly, formal, text-based), with 477 valid responses. Data were analyzed using ANOVA and linear regression. Results show that the interaction between communication direction and sticker type significantly influences perceptions of justice, which positively affects satisfaction and trust after the apology. The findings offer practical implications for LINE sticker creators and users, emphasizing the importance of choosing appropriate sticker types to enhance communication effectiveness. This study contributes to understanding workplace communication and offers strategies to foster better professional relationships through digital expression tools.